Xenopus laevis ribosomal protein genes: isolation of recombinant cDNA clones and study of the genomic organization. - Bozzoni, I (Nucleic Acids Res, 1981)
Poly-A+ mRNA from Xenopus laevis oocytes, partially enriched for r-protein coding capacity has been used as starting material for preparing a cDNA bank in plasmid pBR322. The clones containing sequences specific for r-proteins have been selected by translation of the complementary mRNAs. Clones for six different r-proteins have been identified and utilized as probes for studying their genomic organization. Two gene copies per haploid genome were found for r-proteins L1, L14, S19, and four-five for protein S1, S8 and L32. Moreover a population polymorphism has been observed for the genomic regions containing sequences for r-protein S1, S8 and L14. IMAGES: